The Impact of Interaction Between Credit Risk and Liquidity Risk on Financial Performance of Banks Listed in Damascus Securities Exchange (An Applied Study) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The research aimed to show the impact of credit risk and liquidity risk, and their interaction on financial performance. To achieve that, an applied study was conducted on banks listed on the Damascus Securities Exchange. The sample consisted of eleven banks, excluding Islamic banks due to the lack of data necessary for calculating the liquidity ratio. Data were collected from the annual financial reports of the Damascus Securities Exchange website from 2013-2023. The dependent variable was measured using the return on equity, credit risk using the loan loss provision ratio, and liquidity risk using the ratio of total loans to total deposits.The researcher used the quantitative analytical method, and applied panel data regression models based on PMG/ARDL to estimate the first and second research models, in the Eviews13 program. The research concluded that there is a statistically significant positive impact of liquidity risk on financial performance in long term, while it becomes negative in short term. Credit risk had a significant negative impact on financial performance. And there was a significant negative interaction between credit risk and liquidity risk on banks' financial performance. When the interaction variable is introduced in model, the impact of credit risk on financial performance became positive, and the positive impact of liquidity risk on financial performance decreased.
Keywords: Credit Risk, Liquidity Risk, Financial Performance.